Effects of water deficit at different stages on growth and ear quality of waxy maize - Huang, Chao; Qin, Anzhen; Gao, Yang; Ma, Shoutian; Liu, Zugui; Zhao, Ben; Ning, Dongfeng; Zhang, Kai; Gong, Wenjun; Sun, Mengqiang; Liu, Zhandong (Frontiers in Plant Science, 2023)
Introduction Extreme weather has occurred more frequently in recent decades, which results in more frequent drought disasters in the maize growing season. Severe drought often decreases remarkably plant growth and yield of maize, and even reduces significantly the quality of maize production, especially for waxy maize. Results To study the changes in plant growth, fresh ear yield, and fresh grain quality of waxy maize under water deficits occurring at different growth stages, and further strengthen the field water management of waxy maize, water deficit experiments were carried out under a rain shelter in 2019 and 2020. Water deficit treatments were imposed respectively at the V6–VT (DV6–VT), VT–R2 (DVT–R2), and R2–R3 (DR2–R3) stages of waxy maize, and treatment with non-water deficit in the whole growing season was taken as the control (CK). The lower limit of soil water content was 50% of field capacity for a water deficit period and 65% of field capacity for a non-water deficit period. Results In this study, water deficits imposed at V6–VT and VT–R2 stages decreased plant growth rate and leaf gas exchange parameters, accelerated leaf senescence, and limited ear growth of waxy maize, which resulted in 11.6% and 23.1% decreases in grains per ear, 19.4% and 7.3% declines in 100-grain weight, 20.3% and 14.2% losses in fresh ear yield in 2019 and 2020 growing seasons, respectively, while water deficit at R2–R3 stage had no significant effect on ear traits and fresh ear yield, but the fresh ear yield with husk of DR2–R3 decreased by 9.1% (P<0.05). The obvious water deficit imposed at the V6–VT and VT–R2 stages also lowered grain quality. Water deficits at the V6–VT and VT–R2 stages led to accelerated maturity, resulting in increased total protein, starch, and lysine content in grains at the R3 stage and decreased soluble sugar content. Principal component analysis revealed that when water deficits occurred in the waxy maize growing season, they firstly altered maize physiological processes, then affected ear characteristics and yield, and finally resulted in significant grain quality changes. In conclusion, a water deficit during V6–VT and VT–R2 not only reduced fresh ear yield but also adversely affected grain quality. However, water deficit during R2–R3 had little effect on total protein, starch, and soluble sugar content,but increased obviously lysine content. Discussion The above results suggested that avoiding serious water deficits at the V6–VT and VT–R2 stages of waxy maize while imposing a slight water deficit at the R2–R3 stage has not only little effects on fresh ear yield but also a remarkable improvement in grain quality.